Laparoscopic approach to pelvic organ prolapse – the way to go or a blind alley? - Ewelina Malanowska; Marek Soltes; Andrzej Starczewski; Eckhard Petri; Marcin Jozwik (Videosurgery and Other Miniinvasive Techniques)
Pelvic organ prolapse represents a relatively frequent diagnosis that requires attention due to its detrimental effect on quality of life. Not surprisingly, it is one of the commonest indications for surgery in premenopausal and postmenopausal women, often requiring a complex multidisciplinary approach. Traditional vaginal procedures are being gradually replaced by laparoscopic techniques, offering anticipated benefits in reduced recurrence and complication rates, while respecting the trend towards uterus sparing if desirable. Recently, questions about the safety of alloplastic materials used in pelvic organ prolapse surgery were raised, leading to official restrictions in their use, particularly for transvaginal application. As a result, laparoscopic procedures might appear slightly favored but caution must be taken to assure proper technique of mesh placement while maintaining high awareness of possible long-term mesh-related complications that require close surveillance. Therefore, adequate education and training becomes even more important to achieve optimal results and to avoid possible serious medico-legal charges.